Design of Medical Record Retention Information System Using Visual Studio 2010 at Datu Beru Takengon Hospital, Central Aceh Regency - Sihite, Geovani Arta; Rimanto, Rivaldi (Pascal: Journal of Computer Science and Informatics, 2024)
This research aims to design an information system for the retention of medical records at Datu Beru Takengon Hospital, Central Aceh Regency. The research method used is descriptive with a qualitative approach. The data collection techniques used are by means of interviews, observations and literature studies that are related to the problems faced. As for the software development method, it uses waterfall and uses visual studio 2010. The informant in this study is medical record staff. From the research conducted, it was found that problems such as information systems that are still manual so that they are not effective for report information, so it is necessary to design a database-based information system. The suggestion to overcome this problem is to design a medical record retention application that is able to process medical record data that is no longer used or inactive. So that it can optimize the time for the implementation of medical record retention.